A dual-genotype IDH-mutant infiltrating glioma, a real oligoastrocytoma in cerebral hemisphere - Jing Liu, PhD; Fan Lin, PhD; Yanhua Sun, MM; Xia Liu, MM (IBRO Neuroscience Reports)
Since the 5th edition of CNS WHO classification. the categorization of oligoastrocytoma has been discontinued. It is now understood that the majority of tumors previously identified as oligoastrocytomas can be reclassified into either astrocytomas or oligodendrogliomas based on molecular characteristics. In this report, we present a rare case of true oligoastrocytoma characterized by the coexistence of two distinct cell types within a single tumor mass, as evidenced in imaging findings and histological examination. The left frontal infiltrating glioma displayed calcification, and histological analysis revealed two morphologically distinct regions corresponding to oligodendroglioma and astrocytoma. Immunohistochemical and molecular pathology analyses, including IDH1, ATRX, TP53 mutations, H3K27me3 status, Tert promoter mutations, and 1p/19q co-deletion, are consistent with oligodendroglioma and astrocytoma, respectively. Post-surgery, the patient opted against radiotherapy and chemotherapy and showed no signs of recurrence at a 4-month follow-up, but was subsequently lost to follow-up. This case prompts questions about the prognosis and potential grading criteria for true oligoastrocytoma. It underscores the need for further case studies to potentially re-establish it as a distinct tumor type in future CNS WHO classifications.